Rekonsiderasi Budaya Manumbai Masyarakat Petalangan Melayu Riau Berbasis Al-Qur’an: Februari - Miftah Ulya (STIU Al-Mujtama Pamekasan, 2021)
Manumbai is a tradition of taking honey bee that is familiar to the people of Riau Malay Petalangan. In their view there remains a facet of inner strength, a power which cannot be reached by external effort. The unseen inner strength is greater than the outer strength. Therefore, doing a job with physical strength alone will not be sufficient, without being equipped with the effort to obtain supernatural inner strength. It has been popular that